Resolvin D2 Induces Resolution of Periapical Inflammation and Promotes Healing of Periapical Lesions in Rat Periapical Periodontitis - Siddiqui, Yasir Dilshad; Omori, Kazuhiro; Ito, Takashi; Yamashiro, Keisuke; Nakamura, Shin; Okamoto, Kentaro; Ono, Mitsuaki; Yamamoto, Tadashi; Van Dyke, Thomas E.; Takashiba, Shogo (Frontiers in Immunology, 2019)
Periapical periodontitis results from pulpal infection leading to pulpal necrosis and resorption of periapical bone. The current treatment is root canal therapy, which attempts to eliminate infection and necrotic tissue. But, in some cases periapical inflammation doesn't resolve even after treatment. Resolvins belongs to a large family of specialized pro-resolving lipid mediators that actively resolves inflammation signaling via specific receptors. Resolvin D2 (RvD2), a metabolite of docosahexaenoic acid (DHA), was tested as an intracanal medicament in rats in vivo. Mechanism was evaluated in rat primary dental pulp cells (DPCs) in vitro. The results demonstrate that RvD2 reduces inflammatory cell infiltrate, periapical lesion size, and fosters pulp like tissue regeneration and healing of periapical lesion. RvD2 enhanced expression of its receptor, GPR18, dentin matrix acidic phosphoprotein 1 (DMP1) and mineralization in vivo and in vitro. Moreover, RvD2 induces phosphorylation of Stat3 transcription factor in dental pulp cells. We conclude that intracanal treatment with RvD2 resolves inflammation and promoting calcification around root apex and healing of periapical bone lesions. The data suggest that RvD2 induces active resolution of inflammation with pulp-like tissue regeneration after root canal infection and thus maybe suitable for treating periapical lesions.